2021
DOI: 10.18639/rabm.2021.1237255
|View full text |Cite
|
Sign up to set email alerts
|

New Normal Context in Health Care Settings after COVID-19 Pandemic: A Narrative Literature Review

Abstract: COVID-19 is an infectious disease that rapidly developed into a pandemic status. This deemed a need for new strategies to carry out routine health care activities. The recent practices and adaptations of the system as a response to the pandemic status were called a new normal situation. The aim of the study was to describe principles for adaptation to a new normal context for health care settings in COVID-19 pandemic. This narrative review of literature was conducted based on policy documents, guidelines, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, to start and revive the social and economic sector, people can continue their daily activities while maintaining social distance and personal hygiene [26]. These new system practices and adaptations in response to the pandemic status are called the new normal [4].…”
Section: New Normalmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to start and revive the social and economic sector, people can continue their daily activities while maintaining social distance and personal hygiene [26]. These new system practices and adaptations in response to the pandemic status are called the new normal [4].…”
Section: New Normalmentioning
confidence: 99%
“…In the declining phase of the pandemic, many countries and health authorities are looking for alternative ways to adapt to new conditions, especially those related to the risk of COVID-19 transmission and requests for non-covid services. This new contextual situation is called the new normal era [4]. This new normal life can be interpreted as a life usually lived but with a new pattern, a new lifestyle related to the application of health protocols.…”
Section: Introductionmentioning
confidence: 99%
“…With the increase in our scientific knowledge and understanding on COVID-19 our outlook has changed and we are more capable of dealing with this pandemic with the new Norms. From the beginning of the pandemic, one notable difference between severe and mild-moderate cases of COVID-19 is the onset of excessive inflammation or a 'cytokine storm' in severe patients leading to multiple organ damage and a high mortality rate [25]. It is therefore suggested that more research is needed on the impact of treating patients with drugs to lower the levels of these enzyme proteins.…”
Section: Sars-cov-2 Fatal In Comorbid / Immune-compromised Patientsmentioning
confidence: 99%